Antimicrobial resistance at the human–animal–environment interface: a focus on antimicrobial-resistant Escherichia coli transmission dynamics, clinical implications, and future directions - Fatokun, Omotayo; Selvaraja, Malarvili; Anuar, Haryati; Tengku Jamaluddin, Tengku Zetty Maztura; Syed Ismail, Sharifah Norkhadijah; Mansor, Rozaihan; Shah, Shamsul Azhar; Oranye, Nelson (Veterinary World, 2024)
Understanding and combating antimicrobial resistance (AMR) is increasingly centered on the intricate relationship between humans, animals, and the environment, withEscherichia coli being the main source of AMR-related fatalities worldwide. E. coli, though prevalent in the intestines of humans and warm-blooded creatures, demonstrates wide ecological adaptability in both intestinal and extraintestinal habitats. This study explores the dynamics, implications, and future directions of antimicrobial-resistant E. coli (AREC) transmission and clinical significance. We investigated the spread of antibiotic-resistant strains among humans, animals, and the environment, illuminating the impact of healthcare and agriculture practices, as well as environmental contamination. The implications of AREC infections are addressed, emphasizing the challenges in treatment due to limited antibiotic options, increased morbidity and mortality rates, and economic burdens on healthcare systems and agriculture, as well as the urgent need for a One Health approach to combat AMR through collaborative efforts across disciplines. Proposed future directions encompass enhanced surveillance, innovative antimicrobial stewardship, and alternative treatment modalities.